Effect of calcium and magnesium silicate on the growth of the castor oil plant subjected to salinity levels - de Brito Neto, Jose Felix [UNESP]; Macedo Beltrao, Napoleao de Esberard; Gonsiorkiewicz Rigon, Joao Paulo [UNESP]; Capuani, Silvia [UNESP] (Universidade Estadual de Londrina (UEL), 2012)
Salt stress decreases the osmotic potential of soil solution causing water stress, causing toxic effects in the plants resulting in injuries on the metabolism and nutritional disorders, thus compromising the plant growth, resulting in lower production. The calcium silicate and magnesium can perform the same function as limestone, besides providing silicon to plants, may also contribute to the resistance of plants to salt stress. Thus, the objective of this study was to evaluate the effect of calcium and magnesium silicate on the growth of the castor oil plant BRS Energia cultivated under saline conditions. This study evaluated plant height, stem diameter, number of leaves, leaf area, dry weight of shoot and root, and soil chemical characteristics. There was no interaction between factors of salinity level and of silicate level regarding the evaluated variables. There was a direct relationship between salinity levels and plant growth in height and stem diameter. The K concentration in soil were affected by salinity levels.
Keywords: Salt stress; silicate application; growth; plants